Does market access improve dietary diversity and food security? Evidence from Southwestern Ethiopian smallholder coffee producers - Muhammed Abdella Usman; Daniel Callo-Concha (Agricultural and Food Economics, 2021)
Market access influences the dietary diversity and food security for smallholder households in many ways. In Ethiopia, most smallholders are subsistence farmers who have poor access to markets. This study used primary data from a household survey to examine the relationship between market access and the dietary diversity and food security for 324 smallholder households in the Yayu area of southwestern Ethiopia in early 2018. Multivariate regression analysis showed that households located far from market centers consumed not only less diverse foods but also spend less on food consumption than households located close to market centers. The correlation between market access and food security measured by Household Food Insecurity Access Scale (HFIAS) did not reach statistical significance, nor did the impact of market access on household consumption and dietary diversity through income. Rather, greater market access appeared to encourage smallholder households to rely on market purchases more than their own production to improve the diversity of household consumption. A direct action to improve the market accessibility would be investments in infrastructure to expand rural road connectivity, which would reduce transaction costs and benefit the welfare of smallholder farmers and communities.
Keywords: O12; O13; Q18; 330; Cash crop; Dietary diversity; Ethiopia; Food security; Market access; Yayu agroforestry systems